2010
DOI: 10.2337/db09-1371
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Hyperglycemia and Insulin Usage With the Risk of Cancer in Type 2 Diabetes: The Hong Kong Diabetes Registry

Abstract: OBJECTIVEInsulin has mitogenic effects, although hyperglycemia may be a risk factor for cancer in type 2 diabetes. It remains uncertain whether use of insulin increases cancer risk because of its effect on cell growth and proliferation or decreases cancer risk because of its glucose-lowering effect.RESEARCH DESIGN AND METHODSA 1:2-matched new insulin user cohort on age (±3 years), smoking status, and likelihood of initiating insulin therapy (±0.05) was selected from a cohort of 4,623 Chinese patients with type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
2
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(158 citation statements)
references
References 32 publications
7
148
2
1
Order By: Relevance
“…Nonetheless, the consistency of the observed epidemiological association, including dose-risk gradient, across different studies, designs and populations is notable. In contrast to those previously consistent reports, one recent observational study reported a protective association of reduced risk of cancer with insulin therapy [22], although several methodological concerns limit the interpretation of those results [23,24].…”
Section: Epidemiological Datacontrasting
confidence: 58%
“…Nonetheless, the consistency of the observed epidemiological association, including dose-risk gradient, across different studies, designs and populations is notable. In contrast to those previously consistent reports, one recent observational study reported a protective association of reduced risk of cancer with insulin therapy [22], although several methodological concerns limit the interpretation of those results [23,24].…”
Section: Epidemiological Datacontrasting
confidence: 58%
“…It appears, however, that these rates are similar to those reported in observational studies, such as the Hong Kong Diabetes Registry, where cancer incidence amongst a cohort of type 2 diabetes patients was reported to be 5.8-9.7 per 1,000 person-years [6]. Furthermore, while there may be a potential for limited follow-up, this would be a nondifferential bias, since it would be true for both the control and intensified treatment arms; thus the interpretation of the OR is not affected.…”
supporting
confidence: 79%
“…These risk factors included LDLC-related risk indicators (LDLC !2.80 mmol/l plus TG !1.7 mmol/l, LDLC !2.80 mmol/l plus albuminuria, LDLC R3.80 mmol/l; Yang et al 2012b) and HDL-cholesterol-related risk indicators (HDLC !1.0 and R1.30 mmol/l; Yang et al 2011b). In addition, we adjusted for use of insulin (Yang et al 2010a), metformin (Yang et al 2011b), RAS inhibitors (Yang et al 2009b(Yang et al , 2010c, gliclazide/glibenclamide (Yang et al 2010d), and rosiglitazone/pioglitazone during follow-up (Yang et al 2012c), which was defined as use of the drug from enrollment to the earliest date of HCC, death, or 30 July 2005, whichever came first. In our review of major biases of pharmacoepidemiological analysis in nonclinical trial setting, we demonstrated that time-fixed Cox model analysis with exclusion of prevalent users and adjustment for drug use indication was free of major biases and could reproduce the effect of a drug as reported in clinical trials (Yang et al 2012d).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Diabetes is associated with increased risk of a spectrum of cancers (Yang et al 2012b) with a linear relationship between HbA1c and all-site cancer risk (Yang et al 2010a). In most surveys, among site-specific cancers, HCC ranks second in terms of strength of association with diabetes (El-Serag et al 2006), only preceded by pancreatic cancer (Everhart & Wright 1995).…”
Section: Introductionmentioning
confidence: 99%